Escaping the growth curse the path to stronger corporate strategy - Doz, Yves L.; Wilson, Keeley (Ascent Audio, 2024)
Sustainable company growth isn't just a pipedream. This three-part blueprint is your guide to avoiding the traps that cause growth to stall. As companies mature, their underlying growth naturally slows-this is called the 'growth curse'. It's a pervasive problem that plagues companies, CEOs, and board members alike. In order to safeguard a company's future, a strategic form of governance in which the board plays a more active role on behalf of all stakeholders, must be activated. This book is comprised of three parts. First it shows companies how to identify the traditional traps that hinder growth. The second part provides companies with a blueprint for building their board, defining long-term strategy, and adjustments necessary to serve continued growth. The final part delves into the specific ways that the board and executives must collaborate in relation to strategic renewal. Reimagining the limits of growth and how companies are run as a consequence provides an escape from the 'growth curse' at last.
Online resource; title from title details screen (O'Reilly, viewed September 10, 2024)
Keywords: Sustainable development; Economic development; Business planning; Développement durable; Développement économique; sustainable development; economic development; Audiobooks; Livres audio